The Characteristic of Applying Military Operation Exercises that Support Environmental Sustainability - Kurniadi, Anwar (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Up to now, there is no military operation exercise yet in TNI that applies environmental preservation, even though the rule of commander-in-chief of TNI No. 62/IX/2010 at article 21 contains military operation exercises that support environmental sustainability. The purpose was to know the characteristics of applying military operation exercises that maintain environmental preservation. The research method used descriptive with case study design in military operation exercise in the Indonesian Navy. The results of the characteristic of military operation exercises that supported support environmental sustainability were 1) choosing the exact location that completed by the environmental licensing; 2) collaboration with the local and national government before and after implementation; 3) point to the person in charge that responsible for the damaged replacement result of military operation exercise; 4) predict the environment capacity of the exercise’s area to next exercises; 5) rehabilitation of the damaging of exercise’s area. The recommendation was Commander-in-Chief of TNI must make a new rule and the new Body that responsible for military operation exercises that support environmental preservation. Keywords: TNI, Environmental Sustainability, Military Operation Exercises